The role of sleep deprivation and fatigue in the perception of task difficulty and use of heuristics - Engle-Friedman, Mindy; Mathew, Gina Marie; Martinova, Anastasia; Armstrong, Forrest; Konstantinov, Viktoriya (Sleep Science, 2018)
This study investigated the effects of sleep deprivation on perception of task difficulty and use of heuristics (mental shortcuts) compared to naturally-experienced sleep at home. Methods: Undergraduate students were screened and assigned through block-random assignment to Naturally-Experienced Sleep (NES; n=19) or Total Sleep Deprivation (TSD; n=20). The next morning, reported fatigue, perception of task difficulty, and use of “what-is-beautiful-is-good,” “greedy algorithm,” and “speed-accuracy trade-off” heuristics were assessed. Results: NES slept for an average of 354.74 minutes (SD=72.84), or 5.91 hours. TSD rated a reading task as significantly more difficult and requiring more time than NES. TSD was significantly more likely to use the greedy algorithm heuristic by skipping instructions and the what-is-beautiful-is-good heuristic by rating an unattractive consumer item with a favorable review as poor quality. Those in Total Sleep Deprivation who chose more difficult math problems made this selection to finish the task more quickly in findings approaching significance, indicating use of the speed-accuracy trade-off heuristic. Collapsed across conditions, self-reported fatigue predicted greater perceived difficulty in both the reading task and a visuo-motor task, higher quality rating for the attractive consumer item, and lower quality rating for the unattractive consumer item. Conclusions: Findings indicate sleep deprivation and fatigue increase perceptions of task difficulty, promote skipping instructions, and impair systematic evaluation of unappealing stimuli compared to naturally-experienced sleep.
Keywords: Sleep Deprivation; Fatigue; Perception; Heuristics; Effort-Mental; Decision Making; Motivation